The coating performance of adipic acid modified and methacrylated bisphenol - A based epoxy oligomers - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (WILEY, 2007)
In the present work adipic acid modified and methacrylated bisphenol A based epoxy resins were prepared. The structures of oligomers were characterized by FT-IR. UV curable clear coatings were applied on aluminum substrates. The physical and mechanical properties of UV-cured coatings such as gel content, solvent resistance, hardness, gloss, flexibility and tensile tests were examined. In addition, the thermal behavior of coatings was also evaluated. It is observed that the tensile properties and thermal stabilities of modified epoxy methacrylate coatings mainly depend on the adipic acid content. The best results were obtained with 5 wt% adipic acid modification. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: UV-curing; epoxyacrylate resins; hardness; stress; strain; MECHANICAL-PROPERTIES; HYBRID COATINGS; UV COATINGS; RESINS